Assessing Fluid Responsiveness in Spontaneously Breathing Patients. (14th January 2016) - Miller, Joseph; Ho, Chuan‐Xing; Tang, Joy; Thompson, Richard; Goldberg, Jared; Amer, Ahmed; Nahab, Bashar
Abstract: Objectives: The primary objective of this study was to test if fasting volunteers exhibit fluid responsiveness using noninvasive hemodynamic measurements. The secondary objective was to test a passive leg raise (PLR) maneuver as a diagnostic predictor of fluid responsiveness. Methods: This was a quasi‐experimental design involving healthy volunteers. Subjects were excluded for pregnancy and congestive heart failure. Following a 12‐hour fast, subjects had baseline hemodynamic monitoring recorded using noninvasive, continuous pulse contour analysis. Subjects then had a PLR maneuver performed, followed by an intravenous bolus of crystalloid. A rise in stroke volume ≥ 10% from baseline with the bolus was considered consistent with fluid responsiveness, and the same rise with a PLR was consistent with a positive PLR maneuver. The primary outcome was the change in stroke volume with a fluid bolus. Univariate analysis assessed changes in hemodynamic parameters. Logistic regression analysis determined the test characteristics of the PLR in predicting subjects who were ultimately fluid responsive. Results: Forty subjects completed the study. The mean change in stroke volume with a crystalloid bolus was 19% (95% confidence interval [CI] = 16% to 21%). Thirty‐six (90%) subjects were fluid responsive. The mean PLR response for the overall cohort was 16% (95% CI = 12% to 19%), and 26 (65%) subjects had a positive PLR maneuver. The PLR was 72% sensitive (95% CI = 55% to 85%) and 100% specific (95% CI = 40% to 100%) for predicting the presence of fluid responsiveness. Conclusions: Noninvasive assessment of fluid responsiveness in healthy volunteers and prediction of this response with a PLR maneuver is achievable. Further work is indicated to test these methods in acutely ill patients.